2013
DOI: 10.1007/s10522-013-9428-5
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of adipokines and IGF-1 are associated with skeletal muscle strength of young and old healthy subjects

Abstract: It is known that adipose tissue mass increases with age, and that a number of hormones, collectively called adipokines, are produced by adipose tissue. For most of them it is not known whether their plasmatic levels change with age. Moreover, it is known that adipose tissue infiltration in skeletal muscle is related to sarcopenia and loss of muscle strength. In this study we investigated the age-related changes of representative adipokines and insulin-like growth factor (IGF)-1 and their effect on muscle stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 49 publications
11
64
0
Order By: Relevance
“…The increase of AdipoQ concentrations in the serum with age for bulls is consistent with observations in aging humans [31,32]. In men, this age-related increase of serum AdipoQ concentration is more pronounced than in women.…”
Section: Age-dependent Differences In Adipoq Concentrationssupporting
confidence: 89%
“…The increase of AdipoQ concentrations in the serum with age for bulls is consistent with observations in aging humans [31,32]. In men, this age-related increase of serum AdipoQ concentration is more pronounced than in women.…”
Section: Age-dependent Differences In Adipoq Concentrationssupporting
confidence: 89%
“…In contrast, resistin is linked to inflammation and senescence. For example, the results from a cross-sectional study which included 412 subjects of different ages revealed that in old subjects resistin is inversely associated with muscle strength [37] . In older adults, higher resistin levels have also been found to be associated with cardiovascular events [38] .…”
Section: Discussionmentioning
confidence: 99%
“…These effects increase skeletal muscle insulin resistance, an important factor in the development of type II diabetes, and demonstrate the close link between the metabolic functions of central adipose tissue and skeletal muscle. Considering adiponectin, leptin and resistin concentrations have also been associated with muscle strength (38) it is plausible that with central obesity and changes in the metabolic function of skeletal muscle, its mechanical function also changes.…”
Section: Discussionmentioning
confidence: 99%
“…Greater variation in muscle mass amongst men may contribute to the larger differences in grip strength by BMI category, but the smaller differences in grip strength with increasing WC in women are difficult to explain. Differences in the levels of adipokines in men compared to women have been reported, along with differential associations with muscle parameters (38). However, much remains to be elucidated regarding the interplay of adipokines, inflammatory mediators and traditional endocrine factors such as levels of anabolic hormones.…”
Section: Cross-sectional Associations Between Different Measures Of Omentioning
confidence: 99%